2022
DOI: 10.1097/mph.0000000000002448
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma and Down Syndrome: An Extremely Rare Association

Abstract: Medulloblastoma has a reduced incidence in Down syndrome (DS). This protective characteristic has not been clarified yet. Here, we report the second case of SHH medulloblastoma and DS documented in the literature. A complete surgery was performed followed by reduced craniospinal irradiation dose and adjuvant chemotherapy. No evidence of tumor recurrence was observed. The overall survival was 9.1 years. No family history or physical stigma of other hereditary predisposition syndrome was found. In the elucidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…2 Even though DS is highly linked with cancer predisposition, solid tumors are very rarely reported. 2 In an epidemiology study reported in 1998, Baird and Sadovnick found a 5 to 7 times greater relative risk of developing cancer than in the general population in children, adolescents, and young adults with Down syndrome. 10 However, the distribution of tumor type is fundamentally different, and individuals with DS are 150 and 33 times more likely to develop acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 Even though DS is highly linked with cancer predisposition, solid tumors are very rarely reported. 2 In an epidemiology study reported in 1998, Baird and Sadovnick found a 5 to 7 times greater relative risk of developing cancer than in the general population in children, adolescents, and young adults with Down syndrome. 10 However, the distribution of tumor type is fundamentally different, and individuals with DS are 150 and 33 times more likely to develop acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Various hypotheses have been formulated to explain this protection against various solid tumors, including the possibility that the increase in circulating endostatin concentration in individuals with Down syndrome might offer protection against the growth of solid tumors. 2,15 Furthermore, the lack of inhibitors such as thrombospondin-1 and tumstatin can accelerate tumor growth. 15 Epidemiology data on brain tumors in children with DS are rare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations